Dreamer : [videorecording (DVD)] : inspired by a true story - Gatins, John; Russell, Kurt; Fanning, Dakota, 1994-; Kristofferson, Kris; Shue, Elisabeth (Dream Works Home Entertainment, 2006)
Ben Crane is a Kentucky horse trainer who watches in horror as a championship filly breaks a leg during a practice run. Ordinarily the horse would have to be put down, but today Ben's daughter, Cale, is at the track. Ben impulsively buys the horse, which causes him to lose his job. The rehabilitation process of the horse is almost too much for a farm that's already struggling to survive in a modern economy, but the horse turns out to be a much-needed salve to the nearly broken family, including Ben's wife and father.